OSTEONECROSIS OF JAW IN A PATIENT TRANSITIONING FROM BISPHOSPHONATES TO DENOSUMAB - M, Sivasangkari; L, Shueh Lin (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Osteonecrosis of the jaw (ONJ) is a rare but severe side effect of anti-resorptive therapy with bisphosphonates or RANKligand antibody denosumab in patients with osteoporosis. Most patients with ONJ have a history of prior dental or oral surgical manipulation in contrary to spontaneous ONJ. Median time to development of ONJ varies with the type of bisphosphonate used. ONJ could occur as early as 10 months with intravenous bisphosphonates whereas about 4.6 years with oral bisphosphonates. In Denosumab treated patients the risk of ONJ seemed to plateau between year 2-3 whereas the risk of ONJ increased with duration of use of bisphosphonates. CASE A 66-year-old retired lady nurse with history of premature ovarian insufficiency at the age of 40 years old was noted to be osteoporotic at the age of 48 when she presented with a clavicle fracture. She was initially treated with hormone replacement therapy, raloxifene and subsequently put on alendronate for 9 years duration. She developed fracture of right metatarsal while on alendronate. Thereafter, she was switched to Denosumab for 3 years. She presented with painful swelling over right cheek and jaw for 3 weeks duration. She was confirmed to have ONJ Stage 3 and underwent debridement of necrotic bone of right maxilla. There was also fistula to the right maxillary sinus for which she required recurrent debridement and perioperative antibiotics before complete healing. CONCLUSION Transitioning antiresorptive therapy from bisphosphonate to denosumab may be an additional risk factor for developing ONJ. A study by Voss PJ et all showed those transitioning from bisphosphonate to denosumab had 3 times more relapses of ONJ compared to those on bisphosphonate monotherapy. In these patients, treatment was also associated with complications such as fistula. Continuous surveillance of risk factors and additional dental screening before transitioning should be initiated to prevent ONJ.